Vaccination coverage and immunity against hepatitis B among HIV-infected patients in South Brazil - Martins,Saulo (2015)
Evidence-based strategies to improve the hepatitis B virus (HBV) vaccination coverage rates might help to reduce the burden caused by co-infection with HBV and human immuno-deﬁciency virus (HIV). In this study, the aim was to evaluate the vaccination coverage and immunity against HBV among HIV-infected individuals in South Brazil, and identify factors that are associated with compliance patterns and antibody reactivity. Three hundred HIV-infected men and women were included in this survey. The patients answered a standardized questionnaire, and vaccination cards were checked in order to assess hepatitis B vaccine status. A blood sample was collected for quantitative determination of antibody to hepatitis B virus surface antigen (anti-HBs). Participants were also evaluated for their CD4 cell count and HIV viral load. The overall vaccination coverage of HBV vaccination found in this study (57.4%) was lower than that was previously reported in South Brazil. Anti-HBs levels >10 IU/L were observed in 47.0% of the studied population. A signiﬁcant inequality in the coverage rates and antibody reactivity was found in favor of patients with better economic status. In conclusion, the results indicate the need for improvement in the HBV vaccination coverage among HIV carriers, in particular focusing on low-income individuals.